Improving field legume nodulation by crushing nodules onto seeds: implications for small-scale farmers - Pudasaini, Roshan; Hewedy, Omar A.; Raizada, Manish N. (Frontiers in Agronomy, 2023)
One billion people globally suffer from protein (amino acid) malnutrition. Grain legumes represent a solution. They recruit symbiotic rhizobia bacteria from soil into root nodules, where the rhizobia convert atmospheric nitrogen gas (N2) into ammonia (NH3) which serves as a building block for chlorophyll and protein. However, when a legume species is newly introduced to a region, yields can be low due to incompatible soil rhizobia. Millions of subsistence legume farmers can benefit from inoculation with exotic rhizobia bacteria, but many subsistence farmers especially in Africa do not benefit from commercial inoculants due to real-world constraints. Here, in a sequential series of indoor and outdoor experiments, we show that root nodules (rhizobia habitats) can be harvested and crushed onto legume seeds, ultimately improving nodulation and chlorophyll under field conditions. 16S rRNA metagenomic sequencing confirmed that nodule crushing onto seeds effectively transferred rhizobia to next-generation nodules. Therefore, nodule crushing represents a simple method to diffuse elite rhizobia strains. However, exotic rhizobia come with risks and limitations. Therefore, in addition to diffusing elite rhizobia, we propose that this simple, decentralized technology can also empower smallholders to improve indigenous strains or indigenize exotic strains by repeated nodule crushing from healthy plants.